Humor Construction through Metaphor in a Stand-Up Comedy under Conceptual Blending Theory: A Case Study of The King of Comedy - Liu, Lian; Chen, Hui; Liu, Honggang (Linguistic Exploration, 2026)
Humor is essential in daily life and as linguistic research advances, its mechanisms have attracted increasing scholarly attention. Metaphor as a fundamental way humans conceptualize the world plays a key role in constructing humor. And stand-up comedy, combining verbal artistry with social critique, offers rich naturalistic data for linguistic analysis. To better understand how humor can be constructed through metaphor, this study analyzes the Chinese stand-up comedy program The King of Comedy, using Conceptual Blending Theory (CBT) as the analytical framework. The research aims to investigate how different types of metaphorical blending networks generate humor and to further explore the reasons behind the differences. Through a qualitative analysis of metaphorical humor drawn from the "pure performance" versions of the first three episodes, the study identifies four types of metaphorical blends: simplex networks, mirror networks, single-scope networks, and double-scope networks. The findings reveal that these networks construct humor through role reassignment, structural parallelism, frame dominance, and deep conceptual integration. Moreover, the study argues that the differences in humor construction paths can be attributed to two key factors: the depth of conceptual blending and the emergence of novel structures within the blended mental spaces. By illuminating the cognitive processes behind metaphorical humor, this study not only contributes to a more nuanced understanding of humor construction but also extends the application of CBT to the field of discourse analysis, particularly within the context of live stand-up comedy performances.